2010
DOI: 10.1002/hbm.21091
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive touch differentially activate somatosensory cortex in texture perception

Abstract: The neural mechanisms behind active and passive touch are not yet fully understood. Using fMRI we investigated the brain correlates of these exploratory procedures using a roughness categorization task. Participants either actively explored a surface (active touch) or the surface was moved under the participant's stationary finger (passive touch). The stimuli consisted of three different grades of sandpaper which participants were required to categorize as either coarse, medium, or fine. Exploratory procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 78 publications
6
103
0
Order By: Relevance
“…Similarly, using positron-emission tomography it has been shown that increases in speech production rate result in increased cerebral blood flow in auditory cortices even when auditory feedback was blocked by white noise that was kept constant across rates 20 . Other studies report enhancement of the fMRI signal in S1 during perception of self-generated tactile stimuli compared with similar stimuli externally generated 21,22 . Finally, the fMRI signal in the auditory cortex during active speaking (relative to passive listening) has been shown to be attenuated in STG but enhanced in superior temporal sulcus of the same subjects 23 .…”
mentioning
confidence: 93%
“…Similarly, using positron-emission tomography it has been shown that increases in speech production rate result in increased cerebral blood flow in auditory cortices even when auditory feedback was blocked by white noise that was kept constant across rates 20 . Other studies report enhancement of the fMRI signal in S1 during perception of self-generated tactile stimuli compared with similar stimuli externally generated 21,22 . Finally, the fMRI signal in the auditory cortex during active speaking (relative to passive listening) has been shown to be attenuated in STG but enhanced in superior temporal sulcus of the same subjects 23 .…”
mentioning
confidence: 93%
“…Neural recordings were made while the hand was statically positioned in the desired conformation, allowing us to quantify proprioceptive and multimodal integration effects in the absence of volitional motor commands. Indeed, some studies have examined how cutaneous responses are modulated by active large-scale limb movements (London and Miller, 2013; Shaikhouni et al, 2013; Simoes-Franklin et al, 2011; Weber et al, 2011), or how somatosensory neurons represent active limb position and hand grasping (Debowy et al, 2001; Gardner et al, 2007; Mountcastle and Powell, 1959; Ro et al, 2000). However, it is unclear whether effects are due to endogenous commands enacted by the motor system ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of early reports show that tactile stimulation evokes activation in the parietal operculum [25, 4145]. The parietal operculum and insula (and their subregions) are spatial neighbors [9]; however, these regions have different cytoarchitectonic features [29, 46].…”
Section: Methodsmentioning
confidence: 99%